The political economy of the standard level of services: The role of income distribution - Fabio Fiorillo; Agnese Sacchi (Center for Economic Studies and ifo Institute (CESifo), 2012)
The theory of fiscal federalism points out that decentralisation should be pursued in order to fit differences in individual preferences. However, the presence of externalities and the need of providing merit goods to citizens suggest that centralisation is likely to produce more efficient results. Moreover, in a political economy framework, each decision - including the possibility to fix a standard level of services - mainly depends on the objective function of the policymakers. Adopting this approach, the aim of this paper is to compare the individual convenience of a common standard level defined under a centralised system versus different provisions of public services when decisions are decentralised. Income heterogeneity across individuals is assumed.
Keywords: H70; H73; D31; D78; 330; standard level of services; income concentration; decentralization; cooperative legislature; Öffentliche Dienstleistung; Universaldienst; Zentralstaat; Finanzföderalismus; Public Choice; Einkommensverteilung; Theorie